Isolation and Molecular Characterization of Corynebacterium pseudotuberculosis from Goats in Andaman and Nicobar Islands, India - Jai Sunder; Arun Kumar De; Tamilvanan Sujatha; Gayatri Chakraborty; Srikoti Chandershekhar Mayuri; Debasis Bhattacharya; Rafeeque Rahman Alyethodi; Eaknath Bhanudasrao Chakurkar (Microbiology Research)
Caseous lymphadenitis (CLA), caused by the bacteria Corynebacterium pseudotuberculosis, is a highly contagious disease of small ruminants, especially of goats and sheep. Here, we report an outbreak of the disease in goats for the first time from the Andaman and Nicobar Islands along with isolation and molecular characterization of the pathogen. A total of 22 goats were affected, with an attack rate of 12.02%, and six isolates were identified from the clinical samples. Molecular characterization of the pathogen was carried out based on the sequence information of 16S rRNA and RNA polymerase β subunit (rpoB) gene fragments. rpoB-based phylogenetic analysis indicated that the isolates belonged to Corynebacterium pseudotuberculosis biovar ovis. The antimicrobial resistance study revealed that the isolates were 100% resistant against erythromycin and rifampicin. Fifty percent resistance was found against amoxicillin/clavulanic acid, ciprofloxacin, penicillin, and vancomycin. All the isolates were sensitive to tetracycline, chloramphenicol, cotrimoxazole, sulphafurazole, ampicillin/cloxacillin, and oxytetracycline. In conclusion, the present study reports the occurrence of CLA in goats for the first time from an isolated archipelago of India and unveils the molecular signature and antibiotic resistance patten of the pathogen. The findings of this study will be helpful to control or eradicate the disease from the Andaman and Nicobar Islands.